2021
DOI: 10.1097/mpa.0000000000001760
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Role of F-18 Fluorodeoxyglucose Positron Emission Tomography/Computed Tomography for Characterization of Intraductal Papillary Mucinous Neoplasms

Abstract: Objectives:The purpose of the current study was to investigate the diagnostic performance of F-18 fluorodeoxyglucose (FDG) positron emission tomography (PET) or PET/computed tomography (CT) for characterization of intraductal papillary mucinous neoplasms (IPMN) through a systematic review and meta-analysis. Methods:The PubMed and Embase database were searched for studies evaluating the diagnostic performance of F-18 FDG PET or PET/CT for characterization of IPMN.Results: Across 14 studies (752 patients), the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
(128 reference statements)
0
2
0
Order By: Relevance
“…9,10 PET or PET/CT with 18 F-FDG has shown high diagnostic performance for identifying malignancy in IPMNs and PCLs. 11,12 Pedrazzoli et al 13 reported that PET is more accurate than the ICGs in distinguishing benign from malignant IPMNs, and they suggested that PET should be performed in patients with old age or high surgical risk to avoid the unnecessary resection of benign lesions. However, because of lack of large-scale comparative studies, metabolic information provided by 18 F-FDG PET has not yet been adopted by ICG as other guidelines of the American College of Gastroenterology, American Gastroenterological Association, or European Study Group on Cystic Tumors of the Pancreas.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…9,10 PET or PET/CT with 18 F-FDG has shown high diagnostic performance for identifying malignancy in IPMNs and PCLs. 11,12 Pedrazzoli et al 13 reported that PET is more accurate than the ICGs in distinguishing benign from malignant IPMNs, and they suggested that PET should be performed in patients with old age or high surgical risk to avoid the unnecessary resection of benign lesions. However, because of lack of large-scale comparative studies, metabolic information provided by 18 F-FDG PET has not yet been adopted by ICG as other guidelines of the American College of Gastroenterology, American Gastroenterological Association, or European Study Group on Cystic Tumors of the Pancreas.…”
mentioning
confidence: 99%
“…PET or PET/CT with 18 F-FDG has shown high diagnostic performance for identifying malignancy in IPMNs and PCLs 11,12 . Pedrazzoli et al 13 reported that PET is more accurate than the ICGs in distinguishing benign from malignant IPMNs, and they suggested that PET should be performed in patients with old age or high surgical risk to avoid the unnecessary resection of benign lesions.…”
mentioning
confidence: 99%